Seorang Wanita Usia 73 Tahun dengan Prolaps Uteri Derajat IV : Sebuah Laporan Kasus - Zulfadli, Zulfadli; malia, sherly (CV. Jasa Sukses Abadi, 2024)
Uterine prolapse is a protrusion or lowering of an organ in a woman's pelvic cavity, such as the uterus, bladder, and rectum, while the cause of POP itself is multifactorial. A 73 year old patient came to the Emergency Department (IGD) with complaints of a pink lump coming out of the birth canal without bleeding accompanied by pain in the lower back, and lower abdominal pain which had gotten worse 2 days before entering the hospital. Previously, the patient had felt a lump in his genitals since 2 years ago, the lump came and went, especially when coughing, defecating, doing activities, walking, and standing, and came back by itself when lying down. The patient admitted that he had had a ring installed 1 year ago at RSIA AMC Metro because the patient felt that the lump coming out of his genitals was getting bigger and bigger. For 3 months, the patient has felt that the lump has completely come out and cannot go back in. From the results of the physical examination, the BMI was 26.7, and a pink mass without blood was seen coming out of the vagina. The treatment given to this patient was a total vaginal hysterectomy (TVH).